Do share repurchases distort stock prices? evidence from the United States and Malaysia - Chee, Chong Meng; Ab Razak, Nazrul Hisyam; Amin Noordin, Bany Ariffin (SAGE Publications, 2021)
Heavy share buyback years after the global finance crisis 2008–2009 drew criticism from scholars and financial press that share repurchases were being used by firms to manipulate their stock prices. This paper examines whether a greater firm’s repurchase intensity distorts stock prices reflecting to information. We analyse 2 sets of unbalanced panel data that contain a sample of 337 US and another sample of 167 Malaysian repurchasing firms between 2012 and 2016. Contrary to the criticism, we find that a greater firms’ share buyback intensity in the USA stimulates faster incorporation of information in price and results in more efficient stock prices. The main findings hold true and are robust when an alternative measure of share repurchase intensity was used. The findings of US sample support the notion that share repurchase serves as a signalling tool and price support to promote more efficient stock prices. We also find no strong evidence supporting the notion that shares repurchased by Malaysian firms distort stock prices.